Complex boundary value problems of nonlinear differential equations: Theory, computational methods, and applications - Zhang, Xinguang; Wu, Yong Hong; Covei, D.; Hao, X. (2013)
Editorial to the theme Complex Boundary Value Problems of Nonlinear Differential Equations: Theory, Computational Methods, and Applications